STUDENTS' ATTITUDE TOWARD THE TEACHERS IN ISLAMIC TRADITIONAL SCHOOL (DAYAH) IN ACEH - AR, Muhammad (Englisia Journal, 2013)
This article discusses students' attitude toward the teachers in Traditional Islamic School (Dayah) Aceh. Akhlak (moral, attitude, behavior) is one of the most importance subjects in dayah curriculum that must be taught either for the new students or the senior ones. Dayah (traditional Islamic institution/school) are found throughout Aceh. This institution in another part of Indonesia is called Pesantren. In this institution, most of subjects studied are religious instruction under Syafi'i School of Thought. The students are adviced to study books under Syafiism only. Apart from Syafiism are not allowed. In teaching moral values, the books used are are Taysir al-Akhlak, Ta'lim Muta'allim, and Ihya 'Ulum al-Deen, These books discuss much about how to behave toward teachers, and therefore the students of dayah respect their teachers excessively. The way to respect teachers are spreading Salam when meeting teachers, talk softly with teachers, kissing teachers' hand after shaking hand, and etc. In case of respecting teachers, the students follow not only what they have studied in the books but they follow what they are looking through the attitude of their teachers in the dayah everyday. Therefore, the relationship between students and teachers in dayah are very close any time and anywhere.